Application of Digital Learning Media Through Mentimeter in Increasing Motivation to Learn Arabic in Class XI Religion Students at MAN 2 Ciamis - Maya Ardita; Machmud Yunus; Deni Supriadi; Asep Saprudin; Risa Rahmawati; Balqis A Difinubun; Mamat Rahmat (al-Afkar, Journal For Islamic Studies, 2024)
The title of this research is The Application of Digital Learning Media Through Mentimeter in Increasing Motivation to Learn Arabic in Class XI Religion Students at MAN 2 Ciamias. Applying digital technology can help develop learning skills as well as make learning fun, flexible, participatory, and motivating. Therefore, innovative learning methods with the help of media are essential for the learning process to be interactive and interesting. Thus increasing student learning motivation, among the digital learning media that attracted student attention is the Media Mentimeter. This research aims to learn about the application of digital media through Mentimeters and to understand the learning motivation of students when the media is applied in the learning of Arabic for students of Class XI Religion at MAN 2 Ciamis. The methodology used in this study uses mixed methods. (metode campuran). The results of this study show the application of digital media Effect metering, Effect Metering significantly improves the level of student involvement, improves student understanding of learning material, creates a conducive and supportive learning environment. The student's learning motivation rate was very high with a presentation of 86.90%, students showed a high interest in interactive learning with Mentimeter, felt satisfied with active participation, students engaged in the learning process, increased confidence in understanding the Arabic language material and interest in learning activities using digital media.